The Relationship between Self-Regulated Learning and Self-Efficacy Academic on Academic - Annisa Dwi Kartika; Ros Patriani Dewi; Maghfira Nur Aziza; Ratna Sesotya Wedadjati (Jurnal Multidisiplin Madani, 2024)
This research aims to determine: 1) the relationship between self-regulated learning and academic procrastination in students; 2) the relationship between academic self-efficacy and academic procrastination among students; 3) the relationship between self-regulated learning and academic self-efficacy on academic procrastination in students. The subjects in this research were 93 students at Mercu Buana University, Yogyakarta. Data collection used the Academic Procrastination Scale-Short Form (APS-S), Self Regulated Learning Scale (SRLS), The Academic Self-Efficacy Scale (TASES). The data analysis method uses simple linear regression analysis and multiple linear regression. The research results show that: 1) there is a negative relationship between self-regulated learning and academic procrastination in students, with a correlation value of -0.258 and a p value of 0.012 (p<0.05); 2) there is a negative relationship between academic self-efficacy and academic procrastination in students, with a correlation value of -0.302, F of 9.123 with a p value of 0.003 (p<0.05); 3) there is a relationship between self-regulated learning and academic self-efficacy with academic procrastination in students, with a correlation value of 0.336 and a p value of 0.005 (p<0.01)